MEDIA DIGITAL FLIPBOOK BERBASIS BISINDO UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA TUNARUNGU - Ilhami, Seppa Aulya; Marlina, Marlina; Iswari, Mega; Efrina, Elsa (STKIP Pesisir Selatan, 2025)
This study aimed to develop a digital learning medium in the form of a flipbook integrated with Indonesian Sign Language (Bisindo) to support the early reading skills of students with hearing impairments. The research employed a Research and Development (R&D) approach, adopting a modified 4D model limited to three main stages: define, design, and develop. Data collection instruments included observation sheets, interview guides, expert validation questionnaires (covering media, content, and Bisindo), and student practicality questionnaires. Data were gathered through observation, interviews, and product trials, and analyzed using descriptive qualitative methods. The results demonstrated that the developed digital flipbook was considered valid by experts in terms of content accuracy, visual quality, and its relevance to the learning needs of deaf students. Practicality testing also showed positive responses, with students expressing increased engagement and improved comprehension of reading material through the integration of text, images, and Bisindo videos. The presence of communicative visual elements played a key role in creating a more meaningful and enjoyable learning experience. In conclusion, the Bisindo-based flipbook offers an effective alternative medium to enhance early reading instruction for deaf students in educational settings.